A Practice-Inspired Mindset for Researching the Psychophysiological and Medical Health Effects of Recreational Dance (Dance Sport) - Christensen, Julia F.; Vartanian, Meghedi; Sancho-Escanero, Luisa; Khorsandi, Shahrzad; Yazdi, S. H. N.; Farahi, Fahimeh; Borhani, Khatereh; Gomila, Antoni (Frontiers in Psychology, 2021)
“Dance” has been associated with many psychophysiological and medical health effects. However, varying definitions of what constitute “dance” have led to a rather heterogenous body of evidence about such potential effects. It remains unclear what exact parameters may be driving positive effects. This heterogeneity of evidence is partly due to a lack of a clear definition of dance for such empirical purposes. A differentiation is needed between (a) the effects on the individual when the activity of “dancing” is enjoyed as a dancer within different dance domains (e.g. professional/”high-art” type of dance, erotic dance, religious dance, club dancing, Dance Movement Therapy (DMT), and what is commonly known as hobby, recreational or social dance), and (b) the effects on the individual within these different domains, as a dancer of the different dance styles (solo dance, partnering dance, group dance; and all the different styles within these). Another separate category of dance engagement is, not as a dancer, but as a spectator of all of the above. “Watching dance” has its own set of psychophysiological and neurocognitive effects on the individual. With the help of dance professionals, we first outline some different dance domains and dance styles, and outline aspects that differentiate them, and that may, therefore, cause differential empirical findings when compared regardless (e.g. amount of interpersonal contact, physical exertion, context, cognitive demand, type of movements, complexity of technique and ratio of choreography/improvisation). Then, we outline commonalities between all dance styles. We identify six basic components that are part of any dance practice, as part of a continuum, and review and discuss available research for each of them concerning the possible health and wellbeing effects of these components, and how they may relate to the psychophysiological and health effects that are reported for “dancing”: [1] rhythm and music, [2] sociality, [3] technique and fitness, [4] connection and connectedness (self-intimation), [5] flow and mindfulness, [6] aesthetic emotions and imagination. Future research efforts might take into account the important differences between types of dance activities, as well as the six components, for a more targeted assessment of how “dancing” affects the human body.